Wealth effects and Russian money demand - Aaron Mehrotra; Alexey Ponomarenko (Bank of Finland, Institute for Economies in Transition (BOFIT), 2010)
We examine wealth effects for Russian money demand in a cointegrated vector autoregressive framework. We find that an aggregate wealth variable, as well as the components housing and equity prices included separately, significantly enter the long-run money demand relationship. There are feedback effects from money to wealth. However, the remonetization process lead to high income elasticities even when wealth is included in the model. System instability coincides with the arrival of the global financial crisis in late 2008.
URN:NBN:fi:bof-201408072221
Keywords: 330